Conselho Municipal de Educação em contexto de sistema municipal de ensino: gestão e proposições na/para a educação infantil - RS - Kieling, Guilherme da Silva (2017)
This professional masters dissertation refers to the work of the Education Municipal Council (CME) in the Teaching Municipal System (SME) of Santa Maria-RS, more specifically, to the accreditation and authorization of private schools of pre-school education in a municipal system context, in which there are distances and approximations between their parts/instances/ management. Thus, this master research, as general objective, prioritized to understand how the process of accreditation and authorization of private schools in Santa Maria - RS, in the sense of contributing with the Education Municipal Council for its qualification. The specific objectives were designed to: recognize, from a historical rescue, the emergence and organization of Municipal Education Systems in Brazil and its importance in the policies and management of Early Childhood Education; to understand the importance of a Municipal Education Council in the Municipal Education System, reflecting its participation in the proposal and achievement of public policies for Early Childhood Education and in educational management processes; produce with the Education Municipal Council a guiding document to the Municipal Education System of Santa Maria - RS, related to the process of accreditation and authorization of the operation of private schools of Early Childhood Education; to construct the virtual page of the Municipal Council of Education of Santa Maria – RS. This participant research was methodologically based on the qualitative approach, using theoretical and documentary background, as well as semi-structured interviews with managers of private schools in Santa Maria-RS, besides the participation of the researcher in ordinary meetings and work of the Education Municipal Council and also with the managers of the Teaching Municipal System of Santa Maria (SMED). The difficulties found by the Council regarding the difficulty of accreditation and authorization of the operation of private pre-schools, as well as the supervision and compliance with the norms established in the municipality were considered as a central element in this research, in the sense of finding from the flagged limitations by the individuals involved, possibilities and perspectives to minimize the obstacles and the difficulties of this process in the scenario of the Municipal System of Education in Santa Maria. Therefore, this research resulted in two products that could contribute to the qualification of the educational management processes within the Municipal Education System, among them the elaboration of a draft Instruction containing guidelines to the owners of the private schools of Early Childhood Education regarding process of accreditation and functioning of said schools, as well as the creation and organization of the website of the Council of Education resulting in a mechanism for dialogue and socialization of educational information to the Santa Maria community, in the perspective of access to knowledge, legislation, guidelines and regulations national and local levels regarding Basic Education. These products are based on shared construction among actors and educational scenarios, on transparency, ethics, reliability and quality in the educational management processes by the Board and Institutions added to the SME, as well as on the intentionality of visibility that CME does not yet possess, making this reference collegiate body in Santa Maria and region.